Abnormalities in the Motor Unit of a Fast-Twitch Lower Limb Skeletal Muscle in Huntington's Disease. (November 2019) - Valadão, Priscila Aparecida Costa; de Aragão, Bárbara Campos; Andrade, Jéssica Neves; Magalhães-Gomes, Matheus Proença S.; Foureaux, Giselle; Joviano-Santos, Julliane Vasconcelos; Nogueira, José Carlos; Machado, Thatiane Cristina Gonçalves; de Jesus, Itamar Couto Guedes; Nogueira, Julia Meireles; de Paula, Rayan Silva; Peixoto, Luisa; et al.
Huntington's disease (HD) is a disorder characterized by chronic involuntary movements, dementia, and psychiatric symptoms. It is caused by a mutation in the gene that encodes for huntingtin protein (HTT), leading to the formation of mutant proteins expressed in various tissues. Although brain pathology has become the hallmark for HD, recent studies suggest that damage of peripheral structures also contributes to HD progression. We previously identified severe alterations in the motor units that innervate cervical muscles in 12-month-old BACHD (Bacterial Artificial Chromosome Huntington's Disease) mice, a well-established mouse model for HD. Here, we studied lumbar motoneurons and their projections onto hind limb fast-twitch skeletal muscles (tibialis anterior), which control balance and gait in HD patients. We found that lumbar motoneurons were altered in the HD mouse model; the number and size of lumbar motoneurons were reduced in BACHD. Structural alterations were also present in the sciatic nerve and neuromuscular junctions. Acetylcholine receptors were organized in several small patches (acetylcholine receptor fragmentation), many of which were partially innervated. In BACHD mice, we observed atrophy of tibialis anterior muscles, decreased expression of glycolytic fast Type IIB fibers, and at the ultrastructural level, alterations of sarcomeres and mitochondria. Corroborating all these findings, BACHD animals performed worse on motor behavior tests. Our results provide additional evidences that nerve–muscle communication is impaired in HD and that motoneurons from distinct spinal cord locations are similarly affected in the disease.